2006
DOI: 10.1002/cncr.22432
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of vascular endothelial growth factor protein levels in T1‐2 N0 laryngeal cancer treated with primary radiation therapy

Abstract: BACKGROUND.The purpose of this study was to assess the prognostic value of vascular endothelial growth factor protein levels in a large cohort of patients with T1‐T2 N0 laryngeal cancer treated with primary radiation therapy (XRT).METHODS.Primary tumor specimens from a cohort of 123 patients with T1‐T2 N0 laryngeal cancer treated with XRT between 1975 and 2000 were constructed into a tissue microarray. Clinical prognostic factors included age, sex, T classification, and tumor subsite. Molecular prognostic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 38 publications
1
21
0
3
Order By: Relevance
“…28,29 Many have also argued that the status of p53 is not an appropriate marker for prognosis or clinical outcomes. 13,16,28 We found that NF-jB expression showed the strongest correlation with local tumor control relative to bcl-2 or EGF receptor expression. In our study, nuclear NF-jB expression was also evaluated separately, but it was difficult to determine whether NF-jB was more tightly associated with local recurrence.…”
Section: Discussionmentioning
confidence: 94%
“…28,29 Many have also argued that the status of p53 is not an appropriate marker for prognosis or clinical outcomes. 13,16,28 We found that NF-jB expression showed the strongest correlation with local tumor control relative to bcl-2 or EGF receptor expression. In our study, nuclear NF-jB expression was also evaluated separately, but it was difficult to determine whether NF-jB was more tightly associated with local recurrence.…”
Section: Discussionmentioning
confidence: 94%
“…In another study, VEGF expression was correlated with prognosis in patients with early stage (T1-T2) laryngeal cancer treated with primary radiotherapy. A trend toward higher local relapse was demonstrated in the VEGF positive group, whereas increased VEGF expression was correlated with higher clinical local stage and decreased overall survival [49]. Moreover, VEGF-A expression in another study was reported to be associated with advanced T stage for oral, pharyngeal, and laryngeal squamous cell carcinoma.…”
Section: Vegf and Lymph Node Metastasismentioning
confidence: 86%
“…Statistical analysis of BLID expression in the TMAs was done using SAS version 9.1 (SAS Institute) as we described previously (18)(19)(20). All tests of statistical significance were two-sided.…”
Section: Discussionmentioning
confidence: 99%